The prevalence of brucellosis in indigenous cattle in central Ethiopia - Bekele, T.; Kasali, O.B.; Mukasa-Mugerwa, E.; Scholtens, R.G.; Yigzaw, T. (1989)
Determines the prevalence of brucellosis in indigenous cattle from Gobe and Ghibe (central Ethiopia).